Navigating the digital era: The impact of digitalization and work-life harmony on well-being among solo self-employed individuals - Hyeon Jo; Hyunchul Ahn (PLoS ONE, 2026)
In an era where technological advancements and work-life integration significantly shape the professional landscape, understanding their impact on individual job satisfaction and well-being is crucial, particularly for self-employed business owners. This study explores the effects of digitalization, autonomy, work-life balance, work engagement, and burnout on the job satisfaction and well-being of the self-employed. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on a sample of 12,703 respondents from the Sixth Korean Working Conditions Survey (2020), this research offers comprehensive insights into the unique challenges faced by this demographic. The findings indicate that digitalization and automation significantly increase technology anxiety. In contrast, leadership autonomy and responsibility enhance job satisfaction but adversely impact well-being. Work-life interference negatively affects job satisfaction and well-being but positively correlates with burnout. Conversely, life-work interference positively influences job satisfaction but negatively impacts work engagement. Both work engagement and job satisfaction positively affect well-being, while burnout shows a negative relationship. Notably, work-life time balance positively influences job satisfaction and well-being, and overtime work has a surprisingly positive effect on these aspects. This research contributes to existing literature by underscoring the distinct experiences of the self-employed in the digital age, laying a groundwork for future research.